Investigating incidents of fraud in small economies: the case for Cyprus - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2010)
Abstract: Purpose – The purpose of this paper is to investigate the extent and types of fraud victimization in small economies or specific industries in such economies. In addition, the paper identifies the state of the art in a small economy and considers policy implications. Design/methodology/approach – Drawing on an extensive literature review, a questionnaire was developed, pilot tested and administered to individuals working in 600 randomly selected organizations in Cyprus. Both descriptive and inferential statistics were utilized to analyze the collected data and address the postulated research questions. Findings – It is found that no industry or size of company is immune from fraud. Whilst executives are well aware of fraud, they do not seem to be able to prevent it in their organizations since 85.8 percent are victimized in the last five years. The deterrent impact/effect of both the code of conduct and the audit committee has been investigated. In addition, findings revealed the types of fraud least tolerated as well as those who pose the greatest risk to the local economic environment. Finally, the paper explores the actions taken by local companies when fraud is identified. Research limitations/implications – Owing to the very sensitive nature of the research topic, many respondents felt reluctant to participate, resulting in an 18.83 percent response rate. Practical implications – The findings have a practical relevance to both industry stakeholders and academic scholars who wish to further explore fraud victimization in small economies. Numerous practical implications for the local industry and regulatory authorities are raised regarding fraud precaution and the need for a specialized fraud investigation team as well as forensic accountants is emphasized. Originality/value – Fraud victimization studies have been carried out in bigger economies (G7 or E7) but not in smaller economies. This is the first in-depth attempt to investigate fraud in a small economy in such detail, thus the paper adds to existing knowledge of interest to stakeholders.
Keywords: Crimes; Cyprus; Fraud